Spring report 1999, Rob Thelen - Thelen, Robet al (1999)
An annotated list of birds sighted by Rob Thelen. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1999. Epson - sheet feed